VISUALISASI IBU DAN AYAH DALAM KARYA PATUNG ASSEMBLING - Taufik Ivan Irwansyah Hidayatulloh (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2022)
This research is a study of the creation of sculptures by raising the issue of parents as the main idea carried out by assembling techniques using found materials. Where in the process tried to develop concepts, techniques, and materials for the creation of this work in the form of three statues of Mother and one statue of Father. Aside from the desire to develop this, this creation study seeks to affirm that the figure of both parents becomes very important in the side of life including in its various roles and sacrifices. This creation research is designed as exploratory development research. Therefore, the experimental tendency is to look for possibilities of novelty both in terms of form, technique, and exploration of the material and its medium. Data collection techniques carried out in the form of literature studies include observation as material for empirical studies to obtain relevance between theoretical concept study and the form of experience as a form of reflection in their work. Creating this work broadly carries out several stages including exploration, improvisation, and formation. Various new findings in the process were encountered, and all forms of adjustment between mediums that include materials and techniques were explored with the concept of shape. The medium used includes found material items that are considered non-artistic objects processed through assembling techniques, explored and combined with a concept of creating a work of three sculptures of Mother and one statue of Father into findings from the process so that it becomes an alternative in the study of the creation of this work.Keywords: assembling, found object, Mother, Father. AbstrakPenelitian ini merupakan studi penciptaan karya seni patung dengan mengangkat isu orang tua sebagai gagasan utama yang dikerjakan dengan teknik assembling menggunakan material barang temuan. Di mana dalam prosesnya berusaha mengembangkan konsep, teknik dan material pada penciptaan karya ini dengan wujud tiga patung Ibu dan satu patung Ayah. Selain dari rasa ingin mengembangkan hal tersebut, studi penciptaan ini berusaha menegaskan bahwa figur kedua orang tua menjadi sangat penting dalam sisi kehidupan termasuk dalam berbagai peran dan pengorbanannya. Penelitian penciptaan ini didesain sebagai penelitian pengembangan yang bersifat eksploratif. Oleh karena itu, kecenderungan eksperimentatif untuk mencari kemungkinan-kemungkinan kebaruan baik dari segi bentuk, teknik, eksplorasi material dan mediumnya. Teknik pengumpulan data yang dilakukan berupa studi literatur termasuk observasi sebagai bahan kajian empiris demi memperoleh relevansi antara penelaahan konsep secara teori dengan bentuk pengalaman sebagai wujud refleksi dalam berkaryanya. Proses penciptaan karya ini secara garis besar melakukan beberapa tahapan diantaranya eksplorasi, improvisasi, dan pembentukan. Berbagai temuan baru dalam prosesnya dijumpai, segala bentuk penyesuaian antara medium yang meliputi material dan teknik dieksplorasi dengan konsep kebentukan. Medium yang digunakan meliputi material barang temuan yang dianggap sebagai benda non-seni diproses melalui teknik assembling, dieksplorasi dan dipadukan dengan sebuah konsep penciptaan karya tiga patung Ibu dan satu patung Ayah menjadi temuan dari prosesnya sehingga menjadi alternatif dalam studi penciptaan karya ini.Kata Kunci: assembling, barang temuan, Ibu, Ayah. Author:Taufik Ivan Irwansyah Hidayatulloh : Institut Seni Indonesia Yogyakarta References:Isnanta, S. D. (2015). Penciptaan Karya Seni Mixed Media Berbasis Ekperimentasi Dengan Teknik Assemblage. Abdi Seni : Jurnal Pengabdian Kepada Masyarakat, 6(1), 66–75. https://doi.org/https://doi.org/10.33153/abdiseni.v6i1.2269.Kartika, D. S. (2017). Seni Rupa Modern (Revisi). Yogyakarta: Penerbit Rekayasa Sains.Kelly, J. (2008). The anthropology of assemblage. Art Journal, 67(1), 24–30. https://doi.org/10.1080/00043249.2008.10791291.Marianto, M. D. (2019). Seni & Daya Hidup dalam Perspektif Kuantum. Scritto Book dan BP ISI Yogyakarta.Selly, A. (2019). Galeri Seni Daur Ulang Sampah di Jakarta. Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), I(1), 1–10.Soedarso, S. (2006). Trilogi Seni (Cetakan Pe). Yogyakarta: BP ISI Yogyakarta.Susanto, M. (2011). Diksi Rupa: Kumpulan Istilah & Gerakan Seni Rupa (Revisi). Yogyakarta: DictiArt Lab & Djagad Art House.